Simulated ground motion of the earthquake on Octorber 22nd, 2012, M4.6 at Song Tranh 2 dam area - Thanh, Tran Thi My; Vung, Vi Van; Miyake, Hiroe; Irikura, Kojiro (Vietnam Journal of Earth Sciences, 2016)
Records of ground motion by strong earthquakes are important documents used in earthquake-resistant design, particularly for key construction projects. In reality, there are few records of ground motion caused by maximum earthquakes at major infrastructure facilities, even at locations where strong earthquakes frequently occur with adequate monitoring facilities such as those in Japan, US and Taiwan. To overcome the shortage of raw seismic records at these facilities, there are many simulation studies to model strong earthquake records. This research has been conducted by developed countries to apply to seismic hazard assessment in the important facilities such as hydropower, thermal or nuclear power plants. By the end of 2010, Vietnam has obtained 24 records of ground acceleration of 21 earthquakes (mostly recorded at Tuan Giao and Dien Bien seismic stations). Of these, there are 17 records of earthquakes and the rest are aftershocks of the Dien Bien earthquake on 19 February 2001 with M = 5.3. Song Tranh 2 Hydropower was built in 2010 with a seismic design of the dam of M = 5.5. In reality, the collection of strong motion records above is not enough to select a design ground acceleration for the seismic design of the Song Tranh 2 hydropower plant. In November 2010 Song Tranh 2 hydropower reservoir began water filling. From then to the end of March 2011, the people of North Tra My felt slight tremors and explosive noises, this phenomenon occurred on an increasing frequency. According to the Earthquake Observation Room of the Institute of Geophysics, from 03 November 2011 to March 2014, there were more than 468 earthquakes with magnitude M ≥ 1 occurred near Song Tranh 2 area. Among these, there were 5 earthquake with magnitude greater than M = 4.0 and one M = 4.7; 19 earthquakes with M ≥ 3; 36 earthquakes with M ≥ 2.5. Collection of these records has been very valuable for us to simulate an earthquake of M = 4.6 and compared with observed results. This result confirms that simulation strong ground motion can fully apply in seismic hazard assessment in Vietnam. Song Tranh 2 area we applied the empirical Green’s function method to predict broadband ground motion of earthquake M = 4.6 base on observed records of earthquake M = 3.5. We can also use the recorder earthquake M = 4.6 to simulation design earthquake M = 5.5. References Aki, K., 1967: Scaling Law of Seismic Spectrum, J. Geophys. Res., 72, 1217-1231. Aki, K. và P. G. Richards, 1980: Quantitative Seismology: Theory and Method. M. H. Freeman and Co., New York, San Francisco, p.932. Brune, J. N., 1970: Tectonic Stress and the Spectra of Seismic Shear Waves from Earthquakes, J. Geophys. Pea., 75, 4997-5009. Brune, J. N. 1971: Tectonic Stress and the Spectra of Seismic Shear Waves from Earthquakes, J. Geophys. Res., 76,5002, 1971. Hartzell, S.H., 1978: Earthquake aftershocks as Greens functions, J. Geophys. Res.. 5, 14. Irikura, K., 1983: Semi-Empirical Estimation of Strong Ground Motions During Large Earthquakes, Bull. Disas. Prev. Res. Inst. Kyoto Univ., 33, 63-104. Irikura, K., 1986: Prediction of strong acceleration motion using empirical Green’s function, Proc. 7th Jap. Earthq. Eng. Symp., 151-156. Irikura, K. and K. Kamae, 1994: Estimation of strong ground motion in broad- frequency band based on a seismic source scaling model and an empirical Green’s function technique, Annali Di Geofisica. 37, 6, 1721-1743. Jan Wiszniowski, Nguyen Van Giang, Beata Plesiewicz, Grzegorz Lizurek, Dinh Quoc Van, Le Quang Khoi and Stanislaw Lasocki, 2015: Preliminary Results of Anthropogenic Seismicity Monitoring in the Region of Song Tranh 2 Reservoir, Central Vietnam. Acta Geophysica, Vol 63, No 3, June 2015, 843-862. Kamae. K, Irikura K., 1991: Prediction strong ground motion using a semi-emprical technique. SmiRT 11 Transactions Vol. K, Tokyo, Japan. Kanamori, H. and D. L. Anderson, 1975: Theoretical basis of some empirical relations in seismology, BulL SeismoL Soc. Am., 65, 1073-1096. Miyake, H., Y. Tanaka, M. Sakaue, K. Koketsu, and Y. Ishigaki, 2006: Empirical Green’s function simulation of broadband ground motions on Genkai Island during the 2005 West Off Fukuoka Prefecture earthquake, Earth Planets Space, 58, 1637-1642. Poiata, N., and H. Miyake, 2006: Broadband ground motion simulation of Romanian earthquakes using empirical Green’s function method, Proceedings of the 1st European Conference on Earthquake Engineering and Seismology, p. 506. Sadeghi, H., H. Miyake, and A. Riahi, 2013: Strong ground motion simulation of the 2003 Bam, Iran, earthquake using the empirical Green’s function method, J. Seismol., 17, 297-312 Trần Thị Mỹ Thành, 2006: Mô phỏng trận động đất Điện Biên, M = 5.3. Tạp chí Các khoa học về Trái đất; T.29, 4, tr.342-349. Vung, V., H. Miyake, T. My Thanh, K. Irikura, 2014: Empirical Green’s function simulations towards site-specific ground motion prediction at the Song Tranh 2 dam in Vietnam, AOGS 11th Annual Meeting, Japan, Jul. 28-Aug. 01, 2014, SE24-A006.